EVALUASI STRATEGI PENDEKATAN BALANCED SCORECARD UNTUK MENINGKATKAN PERTUMBUHAN PENDAPATAN RSU HAJI SURABAYA - Sapitri, Lia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to evaluate and to find out how far the success rate of implementation of strategy of Surabaya Hajj General Hospital which is carried out by using balance scorecard approach based on 4 perspectives which include financial perspective, customer perspective, internal business process perspective, and learning and growth perspective so they are consistent with the Surabaya Hajj General Hospital. The research object is conducted in Graha Nuur Afiyah unit. The method in this research is descriptive qualitative method which is a non hypothesis research so it does not formulate hypothesis.It can be concluded from the result of research that the performance achievement of Graha Nuur Afiyah is quite good since all indicators the fourth balance scorecards show the formulated concept can run and can be measured then they are described by a strategy action plan in order to keep on increasing the growth of Graha Nuur Afiyahâs income. The balance scorecard method is already well known in the scope of Graha Nuur Afiyah yet the socialization of the introduction of balance scorecard to all employees is definitely required with regard to understand the importance of the improvement of management performance for the sake of continuity of Graha Nuur Afiyahâs operational activities. Keywords: Balance Scorecard, Strategy, performance Evaluation.